The relationship between technical and physical fitness parameters in swimmers aged 13–14 - Malinovskiy, M.S.; Arishin, A.V.; Pogrebnoy, A.I. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to determine the degree of influence of physical fitness on the kinematic and dynamic parameters of swimming technique in young swimmers aged 13-14. Methods and structure of the study. To assess physical fitness, tests from the Federal Standard for Sports Training in Swimming for the training stage were used, in which 85 swimmers aged 13-14 and with I-II sports qualifications took part. Technical readiness was assessed based on kinematic and dynamic indicators. The data was processed using mathematical statistics methods. Results and conclusions. The data obtained allows us to propose a new conceptual model of the relationship between the physical and technical preparedness of young swimmers, where strength and speed-strength qualities are the basic factors determining the potential for technical mastery. Coordination abilities perform a modulating function, optimising the realisation of strength potential. Flexibility and general endurance play a supporting role, the importance of which may increase at later stages of athletic development. The identified patterns are of practical importance for the construction of the training process. An emphasis on the development of strength and speed-strength qualities in combination with the improvement of intermuscular coordination may become a key direction for optimising training methods for 13-14-year-old swimmers.